Anticipated difficult airway management in a case of hemifacial microsomia - Mutha, Sandeep; Pandit, Shrirang; K., Sushmitha; Phalgune, Deepak (International Journal of Research in Medical Sciences, 2023)
Airway management in paediatric patients with facial abnormalities is challenging for an experienced anaesthesiologist. Both mask ventilation and intubation can be difficult or impossible, especially with associated congenital facial anomalies. Hemifacial microsomia (HFM) is linked with mandibular hypoplasia and temporomandibular joint anomalies. These abnormalities may cause problems for direct laryngoscopy and endotracheal intubation. A case report of a two-year-old child having HFM with a history of failed intubation in the past is presented here. We did manoeuvres for proper fitting of mask and to prevent air leak during mask ventilation. As there was a history of failed intubation, we kept difficult intubation kit including fiberoptic bronchoscopy, video laryngoscopy and ultrasound ready.